Smartphones in clinical practice: doctors' experience at two Dublin paediatric teaching hospitals. (August 2018) - Hadidy, Taha; Alshafei, Abdulrahman; Mortell, Alan; Doherty, Eva
Abstract Introduction We conducted a study at two main centres for paediatric surgery in the Republic of Ireland, Temple Street Children's University Hospital (TSCUH) and Our Lady's Children's Hospital Crumlin (OLCHC). Aim The aim of the study was to assess doctors' opinions, frequency and methods of smartphone use in clinical practice. Methods Doctors (n = 265) at the two hospitals were invited to complete a 12-item survey. Descriptive statistics were calculated accordingly. Results Almost 50% (132/256) responded; 98.4% owned a smartphone and 76% owned an iPhone. Seventy-nine percent used medical apps and 59% used the OLCHC formulary. Ninety-seven percent used smartphones for inter-team communication with 73.5% (n = 97) using WhatsApp. Smartphone camera was used by 57% for clinical photos and 41% for photos of radiological imaging. Only 42% reported obtaining consent for smartphone camera use from patients or guardians. Ninety-two percent either 'strongly agreed' or 'agreed' that smartphones positively impact their practice. Conclusion Smartphone usage is universal among healthcare professionals and their influence is growing in patient care.